An approach to the asthma‐protective farm effect by geocoding: Good farms and better farms. Issue 3 (7th February 2018) - Müller‐Rompa, S. E. K.; Markevych, I.; Hose, A. J.; Loss, G.; Wouters, I. M.; Genuneit, J.; Braun‐Fahrländer, C.; Horak, E.; Boznanski, A.; Heederik, D.; von Mutius, E.; Heinrich, J.; et al.
Abstract: Background: The highly consistent association of growing up on a farm with a reduced asthma risk has so far been attributed to direct farm exposure. In contrast, geographic determinants of the larger environment have never been assessed. In this study, the effects of proximity to farms and environmental variables in relation to the residential address on asthma and atopy were assessed. Methods: Addresses of 2265 children of the Bavarian arm of the GABRIELA study were converted into geocodes. Proximity to the nearest cow farm was calculated, and environmental characteristics were derived from satellite data or terrestrial monitoring. Bacterial diversity in mattress dust samples was assessed in 501 children by sequencing of the 16S rRNA amplicons. Logistic regression models were used to calculate associations between outcomes and exposure variables. Results: Asthma and atopy were inversely associated with the presence of a farm within a radius of maximum 100 m. The environmental variables greenness, tree cover, soil sealing, altitude, air pollution differed not only between farm and non‐farm children but also between farm children with and without another farm nearby. The latter distinction revealed strong associations with characteristics of traditional farms including a broader diversity of microbial exposure, which mainly contributed to the protective effect on asthma. In non‐farm children, the protective effect of a farm nearby was completely explained by consumption of farm milk. Conclusions: Clustering of farms within a neighborhood of 100 m is strongly associated with the protective effect on asthma and may represent a more traditional style of farming with broader microbial exposure. Abstract :